ANALISIS SALURAN DRAINASE DIJALAN BANTAR KOTA TASIKMALAYA - Eful, Andre; SUMARNO, WAHYU; DEFIANA, YANTI (Universitas Majalengka, 2022)
The number of people who increase every year has resulted in the shift of land use in every place, not least in the city of Tasikmalaya. This change in land use indirectly results in reduced water catchment areas so that when it rains with high intensity it will cause inundation. Inundation in urban areas can be caused by several factors, for example due to a disturbed drainage system. The purpose of this study was to determine the condition of the drainage channel on the Bantar street of Tasikmalaya City and to determine the ideal drainage channel to deal with frequent floods.The method used in this research is direct measurement in the field (observation) by taking existing channel data consisting of the coordinates of each channel for each stationing, field contour data, and channel dimensions. Then the data is processed to determine the condition of the drainage channel that will be used for the analysis of the ideal channel capacity to deal with flood problems at the research location.The results of this study can be concluded that the condition of the existing channels on the outskirts of the city of Tasikmalaya some already exist that are not suitable for use, and must be immediately replaced with a more ideal channel so that the water discharge can flow smoothly and the dimensions of the channel are ideal for maximum water flow. on the Bantar City Tasikmalaya road section, the width (b) = 0.8 height (H) = 0.9 and guard height (W) = 0.6 with a drainage coefficient (C) = 0.70, and land slope (s) =0.02.